Clinicopathological study of thyroid swellings in HSK hospital in Karnataka, India - Halbhavi, Subhash N.; Ganjigatti, Mahantayya; Kuntoji, Shrikant B.; Karikazi, Mohammedgouse A. (International Surgery Journal, 2018)
Background: A thyroid enlargement whether diffuses or in the form of nodules have to be investigated to rule out neoplasm. FNAC is the first line of investigation. USG and TFT are also used. The cases which are at high risk are considered for surgery. Aims and objectives of the study was the clinical presentation of thyroid swellings, incidence of various thyroid swelling, benign versus malignant lesion and to correlate the clinical diagnosis with that of pathological diagnosis. Methods: A case series study of 60 patients attending surgical OPD IPD with symptoms of thyroid in SNMRC and HSK hospital Bagalkot between 1-1-2015 to 30-6-2016. After detailed history thorough, clinical examination was carried out all the patients underwent routine investigations TFT FNAC USG neck. Few patients underwent surgery and all the thyroid specimens were sent for HPE and the clinical diagnosis is correlated with that of pathological diagnosis. Results: Of 60 cases female to male ratio was 9:1. The age group involved is between 31-40 years (31.67%). Duration of goiter is less than one year in 60% of cases. The chief complaint was swelling in front of the neck 100%. Duration of swelling ranged from 15 days to 15 years. Toxic features were present in 18.33% of cases, but after TFT the toxic cases were only 6.67%. Most of the patient showed colloid goiter (43.33%) on FNAC. Out of 60 cases only 22 cases did undergo surgery histopathological specimen were colloid versus nodular goiter in 81.88% out of 22 cases only. Conclusions: Thyroid swellings are common in females they occur in 3rd and 4th decade most commonly. FNAC is very useful in the diagnosis. The main indications of surgery are cosmetic problems, pressure effect symptoms are suspicion of malignancy.